Protein NMR Modern Techniques and Biomedical Applications - Berliner, Lawrence.; Berliner, Lawrence. (Biological Magnetic Resonance, 2015)
This book covers new techniques in protein NMR, from basic principles to state-of-the-art research. It covers a spectrum of topics ranging from a “toolbox” for how sequence-specific resonance assignments can be obtained using a suite of 2D and 3D NMR experiments and tips on how overlap problems can be overcome. Further topics include the novel applications of Overhauser dynamic nuclear polarization methods (DNP), assessing protein structure, and aspects of solid-state NMR of macroscopically aligned membrane proteins. This book is an ideal resource for students and researchers in the fields of biochemistry, chemistry, and pharmacology and NMR physics.  Comprehensive and intuitively structured, this book examines protein NMR and new novel applications that include the latest technological advances. This book also has the features of: •                    A selection of various applications and cutting-edge advances, such as novel applications of Overhauser dynamic nuclear polarization methods (DNP) and a suite of 2D and 3D NMR experiments and tips on how overlap problems can be overcome   •                    A pedagogical approach to the methodology   •                    Engaging the reader and student with a clear, yet critical presentation of the applications.